EFISIENSI PENGGUNAAN INPUT DAN SKALA PRODUKSI USAHATANI KOMODITAS KAKAO DI KECAMATAN UDANAWU KABUPATEN BLITAR - Titis Luttiyana; Yuli Hariyati (Jurnal Agribisnis Indonesia, 2019)
Udanawu was one of the cocoa producing areas in Blitar. The average age of cocoa plants in Udanawu was 24 years old, so that if the yield was compared with cocoa plants that were still in their productive age, they were still far away. Cocoa productivity in Udanawu of Blitar was greater than the national cocoa productivity. Whereas when compared with East Java cocoa productivity was smaller than cocoa productivity in East Java. In this case, it was suspected that in the implementation there were factors that support cocoa productivity in Udanawu so that their productivity could be higher than the national cocoa productivity. The data analysis method used was the exponential production function approach with a total sample of 40 farmers. Based on the results of the study showed that: (1) cocoa production in Udanawu of Blitar, as a whole was influenced by land area, labor, chemical fertilizer, organic fertilizer  and pesticides. Of the five variables there was one variable that was significant to the significance value of 5%, namely the land area variable and significant to the significance value of 10%, namely chemical fertilizer. While the other three variables were not significant to the significance value of 5%, namely the variable labor, variable organic fertilizer, and variable pesticide, (2) the scale of production of cocoa farming in the Udanawu of Blitar was on the scale of production (Constant Return to Scale).